2006
DOI: 10.1038/sj.jcbfm.9600229
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Chemokine CCL2 on Blood–Brain Barrier Permeability during Ischemia–Reperfusion Injury

Abstract: The chemokine CCL2 is considered as one of the main effectors driving postischemic infiltration of monocytes into the brain parenchyma. New experimental data, however, suggest that CCL2 could also participate in blood-brain barrier (BBB) 'opening' during the transmigration of monocytes. The current study examines the role of CCL2 in regulating BBB permeability after ischemia in vitro. To address this issue, an in vitro BBB model (coculture of astrocytes and brain endothelial cells) was subjected to 5 h of oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
197
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(204 citation statements)
references
References 52 publications
4
197
1
2
Order By: Relevance
“…Inhibition of adhesion molecules and chemokines reduces experimental stroke damage, in part by depressing recruitment of peripheral inflammatory cells into injured brain (Takami et al, 2001;Zhang et al, 1994;Zhang et al, 1995). For example, the chemokine Ccl2 not only contributes to postischemic inflammation but also confers damage to the blood-brain barrier (Dimitrijevic et al, 2006). In this subcategory, DHT induction of Cox-2 is of interest, as ischemic neuronal damage is enhanced through inflammation and Na + -Ca 2 + homeostasis via activation of E-prostanoid receptor 1 receptor by prostaglandin E 2 (Kawano et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of adhesion molecules and chemokines reduces experimental stroke damage, in part by depressing recruitment of peripheral inflammatory cells into injured brain (Takami et al, 2001;Zhang et al, 1994;Zhang et al, 1995). For example, the chemokine Ccl2 not only contributes to postischemic inflammation but also confers damage to the blood-brain barrier (Dimitrijevic et al, 2006). In this subcategory, DHT induction of Cox-2 is of interest, as ischemic neuronal damage is enhanced through inflammation and Na + -Ca 2 + homeostasis via activation of E-prostanoid receptor 1 receptor by prostaglandin E 2 (Kawano et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Absence of CCR2 and CCL2 owing to treatment with neutralizing antibodies decreases the permeability of the brain endothelial barrier during in vitro ischemia-reperfusion. 51 Furthermore, CCR2-deficient mice are reported to have smaller infarcts, reduced blood-brain barrier permeability and reduced expression of inflammatory cytokines after ischemia-reperfusion compared with wild-type littermate controls. 52 Another study has shown that, compared with wild-type animals, CCR2-deficient mice have reduced levels of macrophages and neutrophils in the ischemic brain after ischemia-reperfusion, but without any difference in infarct volume.…”
Section: Evidence For a Role Of Ccr2 In Central Nervous System Diseasesmentioning
confidence: 99%
“…By binding to their specific Gprotein-coupled receptors, chemokines induce cell-specific migration and activation of immune cells (Glabinski et al, 1996;Hulkower et al, 1993;Lahrtz et al, 1998;Miller and Meucci, 1999). Monocyte chemoattractant protein-1 (MCP1; officially known as C-C motif chemokine 2, CCL2) is one of the most highly and transiently expressed chemokines in many central nervous system (CNS) injuries, including ischemia, hemorrhage and excitotoxic injury (Capoccia et al, 2008;Dimitrijevic et al, 2006;Frangogiannis et al, 2007;Hanisch, 2002;Kim et al, 2008;Morimoto et al, 2008;Sheehan et al, 2007;Yan et al, 2007). The rodent MCP1 differs from the human protein at the C-terminus, with the rodent protein having a longer highly glycosylated Cterminus.…”
Section: Introductionmentioning
confidence: 99%